Customised design of a water-cooled cold plate fabricated by selective laser melting - Ho, Jin Yao (2018)
A water-cooled cold plate which is capable of dissipating up to 320 W of heat while maintaining the surface temperature below 33°C has been successfully fabricated by selective laser melting (SLM) using aluminium alloy, AlSi10Mg, as the base powder due to its high thermal conductivity to specific volume ratio. The cold plate was designed with non-uniform flow channel sizes and cylindrical pillars which served to improve the fluid distribution for enhanced heat transfer. Due consideration was given to prevent warpage, collapse of overhung features and removal of internal support structures in the cold plate design. It was demonstrated that SLM can be used to fabricate a cold plate with well-formed internal flow channels and the cold plate design was able to achieve a relatively uniform surface temperature when subjected to heating by a concentric heat source.